Centronuclear myopathy: histopathological aspects in ten patients with chilfhood onset - ZANOTELI,EDMAR (1998)
Centronuclear myopathy is a rare congenital myopathy. According to the period of onset of signs and symptoms and the degree of muscular involvement three clinical forms are distinguished: severe neonatal; childhood onset; and adult onset. We describe herein the muscle biopsy findings of ten patients with the childhood onset form of the disease including three cases with ultrastructural study. The biopsies disclosed increased nuclear centralization that varied from 25 to 90% of the fibers, type 1 predominance, great variability in fiber diameters, involvement in the internal fiber's architecture, and focal areas of myofilament disorganization. The main histopathologic differential diagnoses included type I fiber predominance, congenital fiber type disproportion, and myotonic dystrophy. The histologic abnormalities in centronuclear myopathy may be due to an arrest of maturation on the fetal myotubular stage. The cause of this arrest remains elusive.